2005
DOI: 10.2174/0929867054864868
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate Synthase Structure, Function and Implication in Drug Discovery

Abstract: Recent methodologies applied to the drug discovery process, such as genomics and proteomics, have greatly implemented our basic understanding of drug action and are giving more input to medicinal chemists, in finding genuinely new targets and opportunities for the development of drugs with original mechanisms of action. In this paper, an example of the successful application of some new techniques to the target enzymes with the Thymidylate Synthase (TS) function is given. The improved knowledge of the complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
70
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 2 publications
0
70
0
Order By: Relevance
“…Epidemiological studies have revealed that smoking, diets and other environmental risk factors play important roles in the development of CRC (Chan and Giovannucci, 2010;Park et al, 2011). However, only a small proportion of individuals exposed to the known risk factors develop CRC, while many cases develop CRC among individuals without those risk factors, which suggest genetic factors also play an important role in the colorectal carcinogenesis (Markowitz and Bertagnolli,metabolism, and thymidylate synthase (TYMS) catalyzes the conversion of deoxyuridine monophosphate (dUMP) to deoxythymidine monophosphate (dTMP) in the DNA synthesis by using 5, 10-methylenetetrahydrofolate as a methyl donor (Costi et al, 2005). This process above is essential for the synthesis of thymidine which is a nucleotide needed for DNA synthesis and repair (Costi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have revealed that smoking, diets and other environmental risk factors play important roles in the development of CRC (Chan and Giovannucci, 2010;Park et al, 2011). However, only a small proportion of individuals exposed to the known risk factors develop CRC, while many cases develop CRC among individuals without those risk factors, which suggest genetic factors also play an important role in the colorectal carcinogenesis (Markowitz and Bertagnolli,metabolism, and thymidylate synthase (TYMS) catalyzes the conversion of deoxyuridine monophosphate (dUMP) to deoxythymidine monophosphate (dTMP) in the DNA synthesis by using 5, 10-methylenetetrahydrofolate as a methyl donor (Costi et al, 2005). This process above is essential for the synthesis of thymidine which is a nucleotide needed for DNA synthesis and repair (Costi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, TS has been investigated widely and currently is considered among the best known drug targets in the anticancer area. 5 Several studies clearly showed the efficacy of the evaluation of intratumoral expression of TS mRNA in predicting the response to 5-FU therapy in patients with breast cancer, 6 colorectal cancer, 7 head and neck cancer, 8 pancreatic cancer, 9 and NSCLC. 10 This association was not reported invariably 11,12 ; however, in most of those studies, an adverse effect of higher TS levels on prognosis was documented in different types of human cancers.…”
mentioning
confidence: 99%
“…Like most eukaryotes, humans depend upon ThyA, so there has been special interest in the enzyme of ThyX-dependent pathogens such as Helicobacter pylori, Campylobacter jejuni, Borrelia burgdorferi, and Treponema pallidum (see reference 22 for a review). ThyX in these organisms is an attractive drug target (4,6,15,23). Eubacterial species in the corynebacterium group are unusual because they have retained the genes for both the ThyA/ DHFR and the ThyX pathways (22,23).…”
mentioning
confidence: 99%